The Biotechnological Potential of Marine Bio-reactives: Isolation and Characterization of Novel Toxins from Polychaeta - Campos, Sónia Cristina da Silva (2022)
As the largest and most ancient habitat on Earth, the marine environment has an immense biodiversity that can become an almost endless span of novel bioproducts. Still, only a few have already been syn- thesized in vitro and commercialised as approved drugs. Venom-derived drugs have shown to be a viable alternative to the expensive and time-consuming process that is the design of synthetic pharmaceuticals. Due to long-term coevolution between predator and prey, proteins with strong activity towards specific targets of recipient organisms were recruited into venoms and poisons. Some Polychaeta, a large class of biodiverse and ubiquitous invertebrates, are known to secrete toxins for predation and defence. The present study focused on Glycera alba, a common Glyceridae (Annelida: Polychaeta) from the Portu- guese estuarine intertidal, whose congenerics, G. tridactyla and G. dibranchiata, are known to be ven- omous. As the first attempt to screen for potential proteinaceous toxins, we extracted and fractionated total protein from the G. alba’s proboscis and skin. The structures were compared histologically con- firming the presence of specialised venom glands in the former, which are bound to reservoir-like struc- tures and ducts connecting to hollow jaws. The SDS-PAGE analysis of protein fractions, obtained by ultrafiltration, disclosed intricate proteomes with different bands between the two organs that can be potentially associated to toxins and permeabilising agents, among other bio-reactives. Regarding the proboscis and the skin specific proteomes, LC-MS/MS-based proteomics and Gene Ontology enrich- ment analysis identified relevant differences related to different molecular and physiological pathways. According to toxicity assays, the higher molecular mass fraction’s toxins/enzymes can exert negative effects onto their prey, with emphasis on cytotoxicity. Altogether, the encouraging findings show that venomous annelids can be important sources of novel bio-reactives, albeit illustrating the challenges of surveying organisms whose genomes and metabolism are poorly understood.